Arterial Disease Ulcers, Part 1: Clinical Diagnosis and Investigation. Issue 1 (January 2015) - Weir, Gregory Ralph; Smart, Hiske; van Marle, Jacobus; Cronje, Frans Johannes
Abstract : PURPOSE: To provide information regarding the clinical diagnosis, assessment, and investigations related to arterial disease ulcers of the lower extremity. TARGET AUDIENCE: This continuing education activity is intended for physicians and nurses with an interest in skin and wound care. OBJECTIVES: After participating in this educational activity, the participant should be better able to: Describe the etiology and pathophysiology of peripheral arterial disease (PAD) and arterial ulcers. Identify the clinical features of PAD and arterial ulcers as a result of arterial insufficiency of the lower limb. Compare assessment modalities to determine the extent of arterial insufficiency and appropriate interventions. ABSTRACT: Arterial disease (peripheral vascular disease) is the result of narrowing of the blood vessel lumen. The classic clinical signs need to be recognized early before progression to arterial predominant disease and limb ischemia. Arterial ulcers or tissue breakdown can result from trauma, infection, or other etiologies with diabetes, smoking, increasing age, and hypertension the most important risk factors. Diagnostic testing starts with a palpable pulse with special investigation including handheld Doppler for ankle brachial pressure index ratios, segmental duplex leg Doppler waveforms, and more specialized procedures, including transcutaneous oxygen saturation.